Analisis Yuridis Terhadap Tindak Pidana Penipuan Dalam Transaksi Elektronik Melalui Media Sosial (Twitter) - Claressia Sirikiet Wibisono; Anajeng Esri Edhi Mahanani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The widespread use of social media among the public has created a new need, namely the urgency to create space for conducting business activities, causing the platform to turn into a place for communication, interaction, as well as a trading space. These changes bring various impacts, one of which is the formation of new types of crime in cyberspace. Fraud in electronic transactions via social media (Twitter) is a crime that targets the internet, computers and related technology as its target. Based on the position of the case, the fraud that occurs can be classified as a crime of computer-related fraud or a crime to gain personal gain and/or harm others. The handling of fraud cases can be carried out using the legal basis contained in Law Number 19 of 2016 concerning Information and Electronic Transactions, namely Article 28 paragraph (1) in conjunction with Article 45 paragraph (2). The use of these two articles is based on the principle of lex specialist derogat legi generali. In addition, if examined using a victimological point of view, victims of fraud cases that occur are included in the category of participating victims where the tendency of victims to be unaware of their attitudes/behaviors in certain circumstances is a reason for someone to act. commit crimes against them. The research method used to answer these problems is normative legal research with a case study approach in the form of legal behavior products.